Correlation between Chemical Composition and Antibacterial Activity of Essential Oils from Fifteen Eucalyptus Species Grown in the Korbous and Jbel Abderrahman Arboreta, North East Tunisia - Ameur Elaissi; Zyed Rouis; Samia Mabrouk; Karima Bel Haj Salah; Mahjoub Aouni; Mohamed Larbi Khouja; Farhat Farhat; Rachid Chemli; Fethia Harzallah-Skhiri (Technological Innovation in Pharmaceutical Research Vol. 5, 2021)
The essential oils of fifteen Eucalyptus species harvested from the Jbel Abderrahman and Korbous arboreta (North East Tunisia) were screened for their antibacterial activities by the agar disc diffusion method. The activity of the Eucalyptus essential oils varied significantly within species and within strains. Eighteen major components as identified by GC/FID and GC/MS were selected for a study of the chemical and biological activity variability. The main one was 1,8-cineole, followed by spathulenol, trans-pinocarveol, ?-pinene, p-cymene, globulol, cryptone, ?-phellandrene, viridiflorol, borneol, limonene and isospathulenol. The chemical principal component analysis identified five species groups and subgroups, where each group constituted a chemotype, however that of the values of zone diameter of the inhibition (zdi) identified six groups of Eucalyptus oils, characterized by their antibacterial inhibition ability. The strongest activity was shown by E. platypus oil against Enterococcus faecalis and by E. lamannii oil against Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli. A correlation between the levels of some major components and the antibacterial activities was observed.